Pregnancy-associated breast cancer (PABC) in young women: a matched case-control study. Issue 1 (31st December 2023) - Zhang, Yanshou; Yang, Zhifen; Wang, Chunyang; Du, Lijia; Liu, Yingru
Abstract : We analyzed the clinical characteristics and prognosis of early pregnancy-associated breast cancer (PABC). In this matched case-control study, the PABC patients and non-PABC patients were recruited from Hebei Breast Disease Treatment Center in a ratio of 1:2, involving 40 PABC patients (10 pregnant women, 30 postpartum women) diagnosed between January 2011 and December 2017, and 80 non-PABC patients with matched tumor staging, age (±3 years), and year of diagnosis (± 2 years). The pathological characteristics, disease-free survival (DFS), and overall survival (OS) were compared between the groups. The first gravidity age in PABC patients was significantly older than that of non-PABC patients (26.8 years vs. 23.5 years, P  < 0.05). Categorized by receptor status, the ratio of hormone receptor (HR)-positive breast cancer was lower in PABC patients than in non-PABC patients (57.5% vs. 70.0%, P  = 0.221), while the incidences of HER2− (42.5% vs. 37.5%, P  = 0.692) and triple-negative breast cancer (20% vs. 12.5%, P  = 0.578) were higher in PABC patients than in non-PABC patients, although no significant differences were detected. Compared with non-PABC patients, PABC patients delivered the first gravidity at an older age, but showed no differences in pathological characteristics, DFS, and OS.